Development and management of gastrointestinal symptoms in long-term COVID-19 - He, Kai-Yue; Lei, Xin-Yuan; Zhang, Lei; Wu, Dan-Hui; Li, Jun-Qi; Lu, Li-Yuan; Laila, Umm E.; Cui, Cui-Yun; Xu, Zhi-Xiang; Jian, Yong-Ping (Frontiers in Microbiology, 2023)
Background Emerging evidence reveals that SARS-CoV-2 possesses the capability to disrupt the gastrointestinal (GI) homeostasis, resulting in the long-term symptoms such as loss of appetite, diarrhea, gastroesophageal reflux, and nausea. In the current review, we summarized recent reports regarding the long-term effects of COVID-19 (long COVID) on the gastrointestine. Objective To provide a narrative review of abundant clinical evidence regarding the development and management of long-term GI symptoms in COVID-19 patients. Results Long-term persistent digestive symptoms are exhibited in a majority of long-COVID patients. SARS-CoV-2 infection of intestinal epithelial cells, cytokine storm, gut dysbiosis, therapeutic drugs, psychological factors and exacerbation of primary underlying diseases lead to long-term GI symptoms in COVID-19 patients. Interventions like probiotics, prebiotics, fecal microbiota transplantation, and antibiotics are proved to be beneficial in preserving intestinal microecological homeostasis and alleviating GI symptoms. Conclusion Timely diagnosis and treatment of GI symptoms in long-COVID patients hold great significance as they may contribute to the mitigation of severe conditions and ultimately lead to the improvement of outcomes of the patients.